Associations between tobacco inhalation and semen parameters in men with primary and secondary infertility: a cross-sectional study - Fan, ShiWei; Zhang, Zeling; Wang, HuiRu; Luo, Lei; Xu, Bo (Frontiers in Endocrinology, 2024)
Objective To examine the impact of tobacco smoking on seminal parameters in men with both primary and secondary infertility. Methods This cross-sectional study analyzed 1938 infertile men from China who were categorized as nonsmokers (n=1,067) and smokers (n=871), with the latter group further divided into moderate smokers (1-10 cigarettes per day) (n=568) and heavy smokers (>10 cigarettes per day) (n=303). We assessed semen volume, concentration, total sperm count, progressive motility, and normal morphology following World Health Organization (WHO 2010) guidelines. A logistic regression model was used to analyze the relationships between smoking and seminal parameters while also controlling for lifestyle factors. Results The analysis demonstrated a statistically significant correlation between smoking and adverse seminal parameters in both primary and secondary infertility patients. Specifically, primary infertile men who smoked had a lower semen concentration, with heavy smokers showing a median sperm concentration of 59.2×10^6/ml compared to 68.6×10^6/ml in nonsmokers (P=0.01). The secondary infertile men who smoked exhibited reduced forward sperm motility, with heavy smokers demonstrating a median progressive motility of 44.7%, which was significantly lower than the 48.1% observed in nonsmokers (P=0.04). Conclusion Smoking is significantly associated with detrimental effects on seminal parameters in infertile men, thus highlighting the need for cessation programs as part of fertility treatment protocols. Encouraging smoking cessation could substantially improve semen quality and fertility outcomes in this population.